2020
DOI: 10.1530/erp-19-0044
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Eosinophilic Myocarditis Presenting with Features of an Acute Coronary Syndrome

Abstract: Summary A 62-year-old female was admitted with severe left-sided chest pain, nausea and pre-syncope. She had widespread T wave inversion on ECG and elevated troponins and was suspected to have an acute coronary syndrome event. Invasive coronary angiogram revealed normal coronary anatomy with no flow-limiting lesions. Echocardiography and cardiac MRI revealed impaired left ventricular (LV) systolic impairment, a mobile LV apical thrombus and a moderate global pericardial effusion with no significant compromise.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Therefore, in our case with chest pain, pronounced eosinophilia levels, and normal coronary computed tomography angiography, the diagnosis of EM should be considered. In some individuals, EM masquerades as acute coronary syndrome, with severe chest pain, electrocardiographic changes, and elevated serum levels of troponins (12). If patients who have hypereosinophilia presenting as acute coronary syndrome only receive stent implantation and anti-angina pectoris, coronary spasm will occur repeatedly and may even lead to sudden death.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in our case with chest pain, pronounced eosinophilia levels, and normal coronary computed tomography angiography, the diagnosis of EM should be considered. In some individuals, EM masquerades as acute coronary syndrome, with severe chest pain, electrocardiographic changes, and elevated serum levels of troponins (12). If patients who have hypereosinophilia presenting as acute coronary syndrome only receive stent implantation and anti-angina pectoris, coronary spasm will occur repeatedly and may even lead to sudden death.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Mosebach et al reported a case of acute myocarditis presenting as an acute coronary syndrome [7]. In 2020, Tran et al studied a case of idiopathic eosinophilic myocarditis presenting with features of an acute coronary syndrome [8]. Viral myocarditis is regarded as a precursor of cardiomyopathy, which results from common viral infections and post-viral immune-mediated responses [9].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of fibrosis shows thickening of involved valve leaflets, and an increase in the intensity of endomyocardial echoes in areas of endomyocardial fibrosis. However, the accuracy of TTE to diagnosis is limited due to highly variable finding associated with myocarditis resulting false negative diagnosis [10]. Coronary angiography does not diagnose the EM, but it helps to rule out acute coronary disease.…”
Section: Introductionmentioning
confidence: 99%